IoT-Based Prepaid Water Meter System with Digital Token for PDAM Customers - Halil Nustadia; Edwar Rosman; Fitri Nova; Hidra Amnur (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2025)
Conventional PDAM water meter systems, which often employ post-paid techniques, frequently lead to payment delinquencies, challenges in consumption regulation, and delayed leak detection. This study creates a prototype of an IoT-enabled prepaid water meter system utilizing the ESP32 microcontroller, YF-S201 flow meter sensor, TDS sensor for water quality assessment, and a relay-operated solenoid valve, combined with a PHP/MySQL website hosted on AWS Academy for digital token transactions and remote monitoring. The technique employs a Research and Development (R&D) framework including analysis, design, implementation, and testing phases. The test findings indicate that the system efficiently conducts real-time monitoring of water consumption and quality while successfully addressing payment arrears; nevertheless, a significant constraint is present in the solenoid valve, which produces an insufficient water flow, failing to satisfy typical home flow rate requirements. The prototype has significant promise for updating PDAM water distribution by offering transparency and comprehensive control to consumers; however, enhancements to the solenoid valve components are necessary before practical adoption